¿Los nuevos cooperantes? relación entre migración remesas y el potencial de los migrantes - Gómez-Schlaikier, Sigrid (2008)
The target of a 38,5% of immigrants in the world is one of the APEC economies. This signifi cant figure should be deeply examined to fi nd out why these destinations are chosen, how immigrants contribute to these economies, how they are benefited when they migrate and how they contribute to their country of origin, such as Peru. This research was conducted on the basis of diverse data about emigration, immigration, remittances and, urban and rural population of the APEC member countries. The international data basically relies on the World Bank reports, while the Peruvian data is based on the information released by the Peruvian National Institute of Statistics and Informatics (INEI). The study seeks to provide new perspectives and to fill out gaps regarding migration and remittances. It also proposes diverse options such as immigration quotas and working visa lotteries in a decentralized manner among APEC economies, and defines the concept of migrant not only as a remittance sender, but also as a potential new aid worker when he returns to his country of origin.